2021
DOI: 10.18502/ijps.v16i2.5820
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of Mobile Phone Abuse (MPA): Exploratory and Confirmatory Factor Analysis in Student Mobile Users

Abstract: Objective: Smartphone is an important technology device in our lifestyle. It has an important part of our daily lives, but it also has a negative effect, such as cell phone dependency. This research aimed to evaluate the psychometric properties of mobile phone abuse (MPA) in the Iranian population. Method: In this study, data were chosen from 1100 participants who were studying in Tehran universities. The principal version of the scale was translated into Persian using the back translation method. All at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…According to reports [ 2 , 3 ], the number of mobile phone netizens in China has reached 825 million, of which 29.24 to 66.14% of high school students have mobile phone dependence. Mobile phone dependence causes damage to the physical and mental problems and social functions of high school students, such as depression, sleep problems, and poor cognitive and reduced learning abilities [ 4 , 5 ]. Therefore, researches on mobile phone dependence are of great significance to the physical and mental health of high school students.…”
Section: Introductionmentioning
confidence: 99%
“…According to reports [ 2 , 3 ], the number of mobile phone netizens in China has reached 825 million, of which 29.24 to 66.14% of high school students have mobile phone dependence. Mobile phone dependence causes damage to the physical and mental problems and social functions of high school students, such as depression, sleep problems, and poor cognitive and reduced learning abilities [ 4 , 5 ]. Therefore, researches on mobile phone dependence are of great significance to the physical and mental health of high school students.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the selected cut-off value, the prevalence of MPA among our sampled adolescents of Henan province in China was 59.13%. Alavi et al ( 52 ) used the Mobile phone abuse questionnaire (MPA) to measure mobile phone usage of students, which showed that the cut-off point was 46 participants (31.2%) who were identified as having mobile phone addiction. The Smartphone Addition Inventory in Spanish (SPAI-Spain) was employed to investigate mobile addiction in a number of university communities in Spain.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria were as follows: Being in 4th to 6th grade of primary school, obtaining a score of 46 or higher from the MPA questionnaire (MPAQ) (13), being in pre-contemplation, contemplation, and preparation stages for MPU, having mental and physical health, and willingness to participate in the study. The exclusion criteria were absent from more than one educational session, incomplete questionnaire, and unwillingness to continue participation in the study.…”
Section: Study Design and Participantsmentioning
confidence: 99%